Analysis of power transfer efficiency of inductive coupled telemetry system for wireless power transfer - Habib, Mohammad Shawkat; Rahman, Md Mizanur Izanur; Arshad, Atika; Khan, Sheroz (IEEE, 2014)
Recent technological advancements in sensors and conditioning electronics are finding applications in many areas including non-contact monitoring in remote areas, in the medical field and better automation in the automotive industry. Such electronics need power sources both through wired and wireless means. Given this, inductive coupling is the most appropriate and potent approach to carry out this job adequately. The benefit of inductive coupling is that, it can be utilized for both telemetry and powering purposes that is to collect the sensed data from the device. This paper explores the power transfer efficiency performance of an inductive coupling system. Design parameters have been simulated for the variation on the load resistor, the tuning of the inductive circuit and the impact on coil orientation has been studied.